Ecology and behavior of the gemsbok at White Sands Missile Range, New Mexico - Saiz, Richard B., author; Decker, Eugene, advisor; Lehner, Philip N., committee member; Welch, Robert D., committee member (Colorado State University. Libraries, 1975)
The gemsbok (Oryx gazella) is a large desert dwelling antelope native to the Kalahari region of southern Africa. Fifty-one have been released at White Sands Missile Range, New Mexico, as part of the exotic mammal introduction program of the New Mexico Department of Game and Fish. The program's goal is to establish huntable populations of foreign big game in areas where conditions are unsuitable for native big game. Gemsbok numbers increased to an estimated population of 100 animals by the end of the field study. They occupied semi-desert shrub and grassland habitats. Foods consumed included mesquite bean pods, desert grasses, tumbleweeds, and yucca leaves. They displayed an amazing ability to survive with little or no drinking water. Gemsbok were not found to compete significantly with the native big game of White Sands Missile Range due to differences in habitat preferences. They are reproducing at a satisfactory rate, and show potential of becoming successfully established in New Mexico.
Covers not scanned.
Keywords: Gemsbok